Integrating the Five-Pillar Philosophy into Pancasila Education Lessons on Diversity to Prevent Child Bullying in Batak Communities - Yezkyna Ringan Pakpahan; Rini Triastuti; Dewi Gunawati (FKIP - Universitas Riau, 2026)
This qualitative case study research aims to describe the philosophical meaning and implementation of the Lima Poda Philosophy in cultivating character to prevent child bullying and to formulate a reconstruction model integrating its values into PPKn learning at SMP Negeri 022 Parbotihan, Humbang Hasundutan Regency. Data were collected through method triangulation, including semi-structured interviews with PPKn teachers and customary figures, non-participant observation, and document analysis, with data validity ensured through source triangulation. Analysis followed the interactive model of data reduction, display, and verification. The findings reveal that the core concept of Lima Poda, Paias (cleanse), is highly relevant to bullying prevention. Paias Rohamu is reconstructed as social empathy to address emotional insensitivity, while Paias Pamatangmu and Parabitonmu are transformed into moral integrity and non-discrimination to prevent physical and appearance-based bullying. Paias Bagasmu and Pakaranganmu are reconstructed into collective responsibility to foster safe school environments. This reconstruction is systematically integrated into Grade VII PPKn learning on diversity through learning objectives, strategies, and steps aligned with Lickona’s moral domains. Overall, Lima Poda represents valuable local wisdom that can serve as a contextual character education model to combat child bullying in schools.